拂袖挥影吧 关注:43贴子:1,174
  • 2回复贴,共1
f(x)=√x
pf(x1)+qf(x2)=p√x1+q√x2
f(px1+qx2)=√(px1+qx2)
p,q大于0,
则,[pf(x1)+qf(x2)]^2-[f(px1+qx2)]^2=
p^2x1+q^2x2+2pq√x1x2-(px1+qx2)
=(p^2-p)x1+(q^2-q)x2+2pq√x1x2
=p(p-1)x1+q(q-1)x2+2pq√x1x2
p+q=1,则
p(p-1)x1+q(q-1)x2+2pq√x1x2
=-(pqx1+pqx2)+2pq√x1x2
由重要不等式得:
(pqx1+pqx2)≥2√pqx1pqx2=2pq√x1x2
所以-(pqx1+pqx2)+2pq√x1x2≤0
所以[pf(x1)+qf(x2)]^2-[f(px1+qx2)]^2≤0
所以[pf(x1)+qf(x2)]≤[f(px1+qx2)]^2


1楼2011-07-15 16:40回复
    展开左式,欲证结论即:
    abx1^2+abx2^2+(a^2+b^2)*x1x2≥x1x2
    即ab(x1^1+x2^2)+(a^2+b^2)*x1x2≥x1x2
    因x1,x2为正实数,故x1^1+x2^2≥2x1x2
    那么左式≥ab(2x1x2)+(a^2+b^2)*x1x2
    =x1x2(a^2+2ab+b^2)
    =x1x2(a+b)^2=x1x2
    成立!


    2楼2011-07-15 16:41
    回复
      抄完把答案发给扣


      来自手机贴吧3楼2011-07-15 19:42
      回复